Computed Tomography Assessment of Tidal Lung Overinflation in Domestic Cats Undergoing Pressure-Controlled Mechanical Ventilation During General Anesthesia - Martins, Alessandro R. C.; Ambrósio, Aline M.; Fantoni, Denise T.; Pinto, Ana Carolina B. C. F.; Villamizar-Martinez, Lenin Arturo; Soares, João H. N.; Otsuki, Denise A.; Malbouisson, Luiz Marcelo S. (Frontiers in Veterinary Science, 2022)
Objective This study aimed to evaluate lung overinflation at different airway inspiratory pressure levels using computed tomography in cats undergoing general anesthesia. Study design Prospective laboratory study Animals A group of 17 healthy male cats, aged 1.9–4.5 years and weighing 3.5 ± 0.5 kg. Methods Seventeen adult male cats were ventilated in pressure-controlled mode with airway pressure stepwise increased from 5 to 15 cmH2O in 2 cmH2O steps every 5 minutes and then stepwise decreased. Respiratory rate was set at 15 movements per minute and end-expiratory pressure at zero (ZEEP). After 5 minutes in each inspiratory pressure step, a 4 seconds inspiratory pause was performed to obtain a thoracic juxta-diaphragmatic single slice helical computed tomographic (CT) image, and to collect respiratory mechanics data and an arterial blood sample. Lung parenchyma aeration was defined as overinflated, normally-aerated, poorly-aerated and non-aerated according to CT attenuation number (-1000 to -900 HU, -900 to -500 HU, -500 to -100 HU and -100 to+100 HU, respectively). Result At 5 cmH2O airway pressure, tidal volume was 6.7 ± 2.2 mL kg-1, 2.1% [0.3%-6.3%] of the pulmonary parenchyma was overinflated and 84.9% [77.6%-87.6%] was normally inflated. Increases in airway pressure were associated with progressive distention of the lung parenchyma. At 15 cmH2O airway pressure, tidal volume increased to 31.5 ± 9.9 mL kg-1 (p<0.001), overinflated pulmonary parenchyma increased to 28.4% [21.2% - 30.6%] (p<0.001), while normally inflated parenchyma decreased 57.9% [53.4%-62.8%] (p<0.001). Tidal volume and overinflated lung fraction returned to baseline when airway pressure was decreased. A progressive decrease was observed in PaCO2 and ETCO2 when the airway pressures were increased above 9 cmH2O (p < 0.001). The increase in airway pressure promoted an elevation in pH (p < 0.001). Conclusions and clinical relevance Ventilation with 5 and 7 cmH2O of airway pressure prevents overinflation in healthy cats with highly compliant chest walls, despite presenting acidemia by respiratory acidosis. This fact can be controlled by increasing or decreasing respiratory rate and inspiratory time.